Macronutrient balancing affects patch departure by guerezas (Colobus guereza). Issue 4 (19th October 2015) - Johnson, Caley A.; Raubenheimer, David; Chapman, Colin A.; Tombak, Kaia J.; Reid, Andrea J.; Rothman, Jessica M.
Abstract : Foraging strategies are central in shaping social structure and grouping patterns in primates. We address Colobus guereza foraging strategies by investigating their patch departure decisions in relation to diet composition and nutrition. We examine whether guerezas are constrained in their intake of food in patches and thereby forage according to a fixed amount strategy that dictates patch departure. Additionally, we assess whether guereza employ a fixed time strategy or attempt to balance nutrients when foraging. We measured food patch occupancy time, intake rates, and analyzed foods for macronutrients, fiber, and condensed tannins. We determined that guerezas do not employ a fixed time foraging strategy; patch residence time varied widely between 1 and 290 min. They also did not depart patches or stop eating when they reached a specific intake of dry mass, macronutrients, or condensed tannins. However, guerezas maintained a macronutrient balance when feeding across patches, and the balance of protein to non‐protein energy (fats and carbohydrates) in patches is the best indicator of time adult guerezas spent feeding in patches. Previous studies have shown that the protein‐to‐fiber ratio is important in predicting food selection for folivores and their biomass; however, we found that guerezas did not maximize protein and minimize fiber intake while foraging in patches, nor did they stay longer in patches with the highest ratio of protein to fiber concentrations. This study raises questions about the nutritional and social implications of patch depletion as a foraging strategy in folivorous monkeys where food limitation predicts competitive and social regimes. Am. J. Primatol. 79:e22495, 2017. © 2015 Wiley Periodicals, Inc.